Diversity management in New Zealand: towards an empirically-based model of employer propensity to manage diversity. (2nd January 2017) - Parker, Jane; Arrowsmith, James; Haar, Jarrod
ABSTRACT: Diversity management (DM) values differences between groups and individuals at work. Research indicates that poorly executed DM can lead to workplace misunderstandings and subvert team working; well-executed, DM can strengthen organisational innovation, customer focus, retention and working relationships, with positive cost, revenue and productivity implications. Little is known about DM or its treatment via human resource management (HRM) in New Zealand (NZ) workplaces, partly reflecting the absence of regular, in-depth inquiry. In this small, service-orientated economy, we draw on a unique, independent survey to explore DM concepts; the perceived nature and evaluation of workplace DM initiatives; and DM challenges and priorities for organisations and employees. Thematic and simple statistical analyses reveal that DM engenders strong views in the workplace but is complex in its practice and perceived impacts in this and wider settings. This has significant implications for HRM thinking and application, including the development of an empirically-based model of employer proclivity to manage diversity. With employee diversity in NZ set to amplify, it also highlights the need for subsequent nationally-representative research.